Increasing Corporate Value Through Managerial and Enterprise Risk Management (ERM) Disclosure - Ni Luh De Erik Trisnawati; Mertyani Sari Dewi; Ni Putu Ari Aryawati (Universitas Pendidikan Ganesha, 2020)
This study aim to explain managerial ownership and enterprise risk management disclosure for corporate value added. Population of this study are manufacture industry which state on Indonesia Stock Exchange were published annual report between 2016 to 2018. Sample of this study are 57 corporates by purposive sampling technique . The analytical method used Moderated Regression Analysis with panel data regression model. The result show that (1) managerial ownership does not affect corporate value. (2) Enterprise risk management disclosure moderation manajerial ownership on corporate value. The result of this study give some implication for corporate managed by owner and disclouse their enterprise risk management has higher value than other by investor.